2018
DOI: 10.1111/jgh.13859
|View full text |Cite
|
Sign up to set email alerts
|

Full‐spectrum versus standard colonoscopy for improving polyp detection rate: A systematic review and meta‐analysis

Abstract: Full-spectrum endoscopy appears as a promising and reliable technology able to significantly decrease the number of adenomas missed and procedural times, while its superiority over standard colonoscopy in terms of adenoma detection rate results is still unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Evidence around electronic highlighting of flat lesions are still lacking[ 33 ]. The use of full-spectrum colonoscopy, with a panoramic 330 degree view of the colon, has not been shown to be superior to standard colonoscopy with regards to ADR through a meta-analysis of eight randomised controlled trials[ 34 ]. Despite this, narrow band imaging has been demonstrated to be effective in endoscopic predictions of histology, reducing costs and avoiding risks associated with polypectomy[ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence around electronic highlighting of flat lesions are still lacking[ 33 ]. The use of full-spectrum colonoscopy, with a panoramic 330 degree view of the colon, has not been shown to be superior to standard colonoscopy with regards to ADR through a meta-analysis of eight randomised controlled trials[ 34 ]. Despite this, narrow band imaging has been demonstrated to be effective in endoscopic predictions of histology, reducing costs and avoiding risks associated with polypectomy[ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…29 No 3: 415-420 newer costly scopes over high-definition (HD)-colonoscopy was not observed [9]. Considering individual devices, while full-spectrum endoscopy (FUSE) showed discording results [10,11], endoscopic add-on devices aimed at improving visualization behind folds were proved to be effective both in terms of ADR and adenoma miss rate (AMR) based on tandem randomized-controlled trials (RCTs) [12,13]. In particular, our group has recently demonstrated the improvement in ADRs with use of distal attachment devices, particularly with endocuff (Endocuff®, Arc Medical Design, Leeds, UK) and in low-performing endoscopists, without clear benefit of one device over another [12].…”
Section: Meta-analysismentioning
confidence: 99%
“…It was found that even though the adenoma and polyp detection rates were not significantly different between the groups, the PVC group had a significantly lower adenoma miss rate (risk ratio 0.35, 0.25–0.48, p < 0.01). What is also interesting in this meta-analysis is that it shows that there was no difference in cecal intubation time between the groups and, most interestingly, the total colonoscopy time was significantly shorter in the PVC group (mean difference: –2.60, 95% CI: –4.60, –0.61; p = 0.01) [ 21 ]. This is somewhat contradictory to many single studies, including our study, which showed prolonged CIT and total colonoscopy time in the PVC group.…”
Section: Discussionmentioning
confidence: 99%